The Influence of Job Insecurity on Innovative Work Behavior for Outsourcing Employees - Sarah Maulidina (Analitika: Jurnal Magister Psikologi UMA, 2022)
The purpose of this study was to analyze the effect of job insecurity on innovative work behavior in outsourced employees. This study used all outsourced employees at STO Telkom Cinta Damai as many as 120 people as research subjects. The study was analyzed using simple linear regression using the SPSS program. The results showed that there was a negative influence between job insecurity and innovative work behavior on outsourced employees by 0.196. From the results of the analysis, it is also known that job insecurity contributes as much as 3.8% to innovative work behavior in outsourced employees at STO Telkom Cinta Damai. Based on research findings, it is known that job insecurity negatively affects innovative work behavior in outsourced employees at STO Telkom Cinta Damai by 3.8%, while the remaining 96.2% is influenced by other factors.